2011
DOI: 10.1098/rspb.2010.2302
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary morphological diversification of passerine birds introduced to the Hawaiian archipelago

Abstract: Species that have been introduced to islands experience novel and strong selection pressures after establishment. There is evidence that exotic species diverge from their native source populations; further, a few studies have demonstrated adaptive divergence across multiple exotic populations of a single species. Exotic birds provide a good study system, as they have been introduced to many locations worldwide, and we often know details concerning the propagule origin, time of introduction, and dynamics of est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 50 publications
1
48
1
Order By: Relevance
“…House sparrow populations from other introduced ranges, such as North America [34], New Zealand [42] and Hawaii [75], have also shown substantial morphological divergence. The latter study has also shown that morphological divergence was mainly due to selection and not genetic drift.…”
Section: Discussionmentioning
confidence: 99%
“…House sparrow populations from other introduced ranges, such as North America [34], New Zealand [42] and Hawaii [75], have also shown substantial morphological divergence. The latter study has also shown that morphological divergence was mainly due to selection and not genetic drift.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rates of evolutionary divergence upon colonization of oceanic islands, as well as the relative roles of drift and selection in driving this divergence are still poorly understood [9], [10]. Natural selection can quickly modify morphological traits following colonization of a new island or isolated habitat type as has been shown in mammals [11] and birds [12], [13], yet the rate and magnitude of change can also be slow and depend strongly on the taxonomic group [14], [15]. In turn, some phenotypic traits can rapidly change in some cases [16], [17], yet can also show limited differentiation over millions of years [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been tremendous efforts to produce a unified theory of body size evolution on islands (that is, island rule -Foster, 1964;Boback, 2003;Meiri, 2007;Meiri et al, 2006Meiri et al, , 2008Aubret, 2012), very few comprehensive studies have succeeded at precisely identifying body size evolutionary drivers and quantifying the rates at which such evolutionary shifts may occur, especially over relatively short time scales (but see Grant and Grant, 2006;Herrel et al, 2008;Garcia-Porta and Ord, 2013). Body size shifts were nevertheless shown to occur rapidly (that is, from a few decades up to several thousands of years) following colonisation in mammals (Millien, 2006), birds (Mathys and Lockwood, 2011) and reptiles (Aubret and Shine, 2007;Herrel et al, 2008). Further, although many forms of plastic responses, including altered behaviours, feeding strategies and defence mechanisms, were invoked in the successful colonisation of new environments (including islands; Ehrlich, 1989;Stearns, 1989;Via et al, 1995;Holway and Suarez, 1999;Pigliucci and Murren, 2003;West-Eberhard, 2003;Aubret et al, 2004a, b;Yeh and Price, 2004;Fitzpatrick, 2012), the idea that adaptive plasticity may also alter rates of evolution remains very much debated, perhaps because empirical support is scarce (Hinton and Nowlan, 1987;Ancel, 2000;Price et al, 2003;Yeh and Price, 2004;Borenstein et al, 2006;Anderson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%